The complete mitochondrial genome analysis of the stonefly, Flavoperla sp. (Plecoptera: Perlidae). Issue 1 (3rd July 2019) - Wang, Ying; Cao, Jinjun; Chen, Mengdan; Li, Weihai
Abstract: Flavoperla is a small genus in Acroneuriinae, which was established by Chu but was treated as a synonym for a long time until Uchida and Harper recognized Flavoperla as a valid genus. This genus includes 15 species in the world now, including six species from China. Here, we sequenced and annotated the mitochondrial genome of Flavoperla sp. under the next-generation sequence technology, the first representative of Genus Flavoperla . The complete mitochondrial genome of Flavoperla sp. is 15, 796 bp in length with an A + T content of 68.3% showed a positive AT-skew (0.037) and a negative GC-skew (−0.262). The gene order and organization of the mitochondrial genome is consistent with other stoneflies. The control region had the highest A + T content. Eleven PCGs started with the typical codon (ATN), the remaining PCGs started with TTG (ND1and ND5). All PCGs terminated with TAA/TAG, except COII and ND5 used single T. The phylogenetic tree by maximum likelihood (ML) and Bayesian (BI) methods supported that Flavoperla sp. was the sister group to Niponiella limbatella .